Tunnel transition mechanism support all types of NAT users - Nian-feng LU; Zhen-xing WANG; Hui-sheng LIU (Tongxin xuebao)
Through the analied of current tunneling mechanism,a more efficient and applicable tunneling mechanism called TrNAT based on TSP to face different scenarios was proposed.Optimization of the communications between NAT users was achieved with ideology of MIPv6.Then,Shim6 was utilized to realize route redundancy and also improved the route aggregation of 6 to 4 tunnel.Finally,TrNAT tunneling mechanism was implemented on Linux kernel and validated by experiments.